“JUST THE MATHS” UNIT NUMBER 14.6 PARTIAL DIFFERENTIATION 6 (Implicit functions) by A.J.Hobson 14.6.1 14.6.2 14.6.3 14.6.4 Functions of two variables Functions of three variables Exercises Answers to exercises UNIT 14.6 - PARTIAL DIFFERENTIATION 6 IMPLICIT FUNCTIONS 14.6.1 FUNCTIONS OF TWO VARIABLES The chain rule, encountered earlier, has a convenient application to implicit relationships of the form, f (x, y) = constant, between two independent variables, x and y. It provides a means of determining the total derivative of y with respect to x. Explanation Taking x as the single independent variable, we may interpret f (x, y) as a function of x and y in which both x and y are functions of x. Differentiating both sides of the relationship, f (x, y) = constant, with respect to x gives ∂f dx ∂f dy . + . = 0. ∂x dx ∂y dx In other words, ∂f dy ∂f + . = 0. ∂x ∂y dx Hence, ∂f dy ∂x = − ∂f . dx ∂y 1 EXAMPLES 1. If f (x, y) ≡ x3 + 4x2 y − 3xy + y 2 = 0, determine an expression for Solution dy . dx ∂f ∂f = 3x2 + 8xy − 3y and = 4x2 − 3x + 2y. ∂x ∂y Hence, dy 3x2 + 8xy − 3y =− 2 . dx 4x − 3x + 2y 2. If f (x, y) ≡ x sin(2x − 3y) + y cos(2x − 3y), determine and expression for Solution dy . dx ∂f = sin(2x − 3y) + 2x cos(2x − 3y) − 2y sin(2x − 3y) ∂x and ∂f = −3x cos(2x − 3y) + cos(2x − 3y) + 3y sin(2x − 3y). ∂y Hence, dy sin(2x − 3y) + 2x cos(2x − 3y) − 2y sin(2x − 3y) = . dx 3x cos(2x − 3y) − cos(2x − 3y) − 3y sin(2x − 3y) 14.6.2 FUNCTIONS OF THREE VARIABLES For relationships of the form, f (x, y, z) = constant, let us suppose that x and y are independent of each other. 2 Then, regarding f (x, y, z) as a function of x, y and z, where x, y and z are all functions of x and y, the chain rule gives ∂f ∂x ∂f ∂y ∂f ∂z + . + . = 0. ∂x ∂x ∂y ∂x ∂z ∂x But, ∂x ∂y = 1 and = 0. ∂x ∂x Hence, ∂f ∂f ∂z + . = 0, ∂x ∂z ∂x giving ∂f ∂z ∂x ; = − ∂f ∂x ∂z and, similarly, ∂f ∂z ∂y . = − ∂f ∂y ∂z EXAMPLES 1. If f (x, y, z) ≡ z 2 xy + zy 2 x + x2 + y 2 = 5, determine expressions for dz dx and dz . dy Solution ∂f = z 2 y + zy 2 + 2x, ∂x 3 ∂f = z 2 x + 2zyx + 2y ∂y and ∂f = 2zxy + y 2 x. ∂z Hence, ∂z z 2 y + zy 2 + 2x =− ∂x 2zxy + y 2 x and ∂z z 2 x + 2zyx + 2y =− . ∂y 2zxy + y 2 x 2. If f (x, y, z) ≡ xey determine expressions for dz dx and 2 +2z , dz . dy Solution ∂f 2 = ey +2z , ∂x ∂f 2 = 2yxey +2z , ∂y and ∂f 2 = 2xey +2z . ∂z Hence, 2 ∂z ey +2z 1 =− 2 +2z = − y ∂x 2xe 2x and 2 ∂z 2yxey +2z =− = −y. ∂y 2xey2 +2z 4 14.6.3 EXERCISES 1. Use partial differentiation to determine expressions for dy dx in the following cases: (a) x3 + y 3 − 2x2 y = 0; (b) ex cos y = ey sin x; (c) sin2 x − 5 sin x cos y + tan y = 0. 2. If x2 y + y 2 z + z 2 x = 10, where x and y are independent, determine expressions for ∂z ∂z and . ∂x ∂y 3. If xyz − 2 sin(x2 + y + z) + cos(xy + z 2 ) = 0, where x and y are independent, determine expressions for ∂z ∂z and . ∂x ∂y 4. If r2 sin θ = (r cos θ − 1)z, where r and θ are independent, determine expressions for ∂z ∂z and . ∂r ∂θ 5 14.6.4 ANSWERS TO EXERCISES 1. (a) dy 4xy − 3x2 = 2 ; dx 3y − 2x2 (b) dy ex cos y − ey cos x = x ; dx x sin y + ey sin x (c) dy 5 cos x cos y − 2 sin x cos x = . dx 5 sin xsiny + sec2 y 2. ∂z 2xy + z 2 =− 2 ∂x y + 2zx and ∂z x2 + 2yz =− 2 . ∂y y + 2zx 3. ∂z yz − 4x cos(x2 + y + z) − y sin(xy + z 2 ) =− ∂x xy − 2 cos(x2 + y + z) − 2z sin(xy + z 2 ) and ∂z xz − 2 cos(x2 + y + z) − x sin(xy + z 2 ) =− . ∂y xy − 2 cos(x2 + y + z) − 2z sin(xy + z 2 ) 4. ∂z 2r sin θ − z cos θ = ∂r r cos θ − 1 and ∂z r2 cos θ + rz sin θ = . ∂θ r cos θ − 1 6